PENGARUH INTELLECTUAL CAPITAL TERHADAP FIANANCIAL PERFORMANCE PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI (Periode 2014-2015) - Ari Widiyawati (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to examine the influence of intellectual capital on the financial performance of banking companies (ROA) in both the current and the future years. Applying the Pulic model of Value Added Intellectual Coefficients (VAIC), this study attempts to examine the correlation between the efficiency of VAIC in terms of three major resources (physical assets, human capital, and structural capital) and the financial performance of the company's Return on Assets (ROA). The research samples are taken from 29 annual reports of banking companies listed in the Indonesia Stock Exchange in 2014-2015, and the data are analyzed through multiple linear regression method. The results of the study show that the intellectual capital measured by VAIC influences the banking financial performance. The components of intellectual capital that significantly affect the financial performance are Value Added of Human Capital (VAHU) and Value Added of Capital Employed (VACA); whereas, Structural Value Added (STVA) has no significant effect on the banking financial performance.Keywords: Intellectual capital; Financial performance.